Boron Reduced Copper Excess-Induced Oxidative Damage in Citrus sinensis by Modulating Reactive Oxygen Species and Methylglyoxal Formation and Their Detoxification Systems - Xu-Feng Chen; Huan-Huan Chen; Wei-Lin Huang; Wei-Tao Huang; Zeng-Rong Huang; Lin-Tong Yang; Xin Ye; Li-Song Chen (MDPI AG, 2024)
Citrus is mainly cultivated in acid soil with low boron (B) and high copper (Cu). In this study, Citrus sinensis seedlings were submitted to 0.5 (control) or 350 μM Cu (Cu excess or Cu exposure) and 2.5, 10, or 25 μM B for 24 weeks. Thereafter, H2O2 production rate (HPR), superoxide production rate (SAPR), malondialdehyde, methylglyoxal, and reactive oxygen species (ROS) and methylglyoxal detoxification systems were measured in leaves and roots in order to test the hypothesis that B addition mitigated Cu excess-induced oxidative damage in leaves and roots by reducing the Cu excess-induced formation and accumulation of ROS and MG and by counteracting the impairments of Cu excess on ROS and methylglyoxal detoxification systems. Cu and B treatments displayed an interactive influence on ROS and methylglyoxal formation and their detoxification systems. Cu excess increased the HPR, SAPR, methylglyoxal level, and malondialdehyde level by 10.9% (54.3%), 38.9% (31.4%), 50.3% (24.9%), and 312.4% (585.4%), respectively, in leaves (roots) of 2.5 μM B-treated seedlings, while it only increased the malondialdehyde level by 48.5% (97.8%) in leaves (roots) of 25 μM B-treated seedlings. Additionally, B addition counteracted the impairments of Cu excess on antioxidant enzymes, ascorbate-glutathione cycle, sulfur metabolism-related enzymes, sulfur-containing compounds, and methylglyoxal detoxification system, thereby protecting the leaves and roots of Cu-exposed seedlings against oxidative damage via the coordinated actions of ROS and methylglyoxal removal systems. Our findings corroborated the hypothesis that B addition alleviated Cu excess-induced oxidative damage in leaves and roots by decreasing the Cu excess-induced formation and accumulation of ROS and MG and by lessening the impairments of Cu excess on their detoxification systems. Further analysis indicated that the pathways involved in the B-induced amelioration of oxidative stress caused by Cu excess differed between leaves and roots.